Investing in Human Resources for Equitable Education - Madeira, Pascoal Soares (Asian Journal of Multidisciplinary Research, 2025)
Education is not a power struggle or a privileged group, as politicians often do by dividing them by color, party, or ideology. Education is inclusive, global, and transparent. For education to improve, investment in knowledge through human action is necessary, enabling them to understand school management and leadership. To improve schools in the areas of science, advanced skills, and in-depth knowledge, school administrators must understand school management, teacher engagement, financial management, pedagogical management, administrative management, student intellectual growth, and other important government contributions that support the teaching and learning process in schools that focus on qualifications for the national interest within a country. Education is not intended to teach people to behave badly in society, nor is it merely rhetorically transforming society into an intelligent, peaceful, developed, and qualified society. Real action is crucial to demonstrate true quality.